A study on performance management to be a successful in event management / Syahirah Osman - Osman, Syahirah (2009)
These case studies explore the performance management to be successful in event management by Siti Khadijah Ibrahim (SKI) production and marketing (M) sdn bhd and the theories. Performance management objectives of the Company should provide the achieve target and goal, the organization clear about mission and vision. Focused on determining the prevalence and perceived effectiveness of performance in event management and organization to make project management success and running smooth Next, the Company should evaluating the event based upon these goals is essential to measuring the performance in the organization. Often the only measurement criteria for an event are the profit at the end of the day. To make sure all team member understand definition of performance to improve and perform better. The main issue of this study is to explore the performance management to be success in event management taken by SKI production and marketing to improve performance and avoid project fail or delay. This issue deeply explained in the report in order to be more clarifying for understanding of performance management. Some of the suggestions have been explained in enhancing the performance management that are practiced in SKI Production and marketing sdn bhd.